Determination of vitamin C in fruits by using ion chromatography and titration method - 271339 Ahmad Nazmi Roslan; Abdull Rahim Mohd. Yusoff; Fakulti Sains (2010)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2010